دراسة أثر مبيد فوستيل الألمنيوم في مسبب مرض الذبول الوعائي على البندورة Fusarium oxysporum f.sp. lycopersici مخبرياً وأعراض الإصابة حقلياً - طويل محمد; المغربي صباح; القبيلي ميس (Latakia University Journal -Biological Sciences Series, 2019)
The aim of this research was to study of the effect of fosetyl aluminum fungicide in the mycelial growth and conidia spores germination for five isolates of Fusarium oxysporum f.sp. lycopersici in vitro in Tishreen University, Agriculture faculty, pesticides laboratory during 2017 and 2018 years. The fungicide was used with different concentrations from 1 to 2000 parts per million (ppm) (active ingredient) within the nutrient culture (PDA). It also was studied the fungicide effect in reducing the incidence of vascular wilt disease in vivo in Jablah during 2018 spring. The fungicide had applied curatively by Irrigation. It was studied its role in inducing of some resistance indicators. The effect of the fungicide observed only at 2000 ppm, where it inhibited the growth by 17.9 and 42.3% and spores germination by 14.5 to 20.4%. The fungicide efficacy was 65.34% after 60 days of treatment in vivo. The fungicide had an important role in inducing the peroxidase activity and polyphenol oxidase during 15 and 30 days of treatment. Peroxidase activity increased by 2.54 and 2.07 times compared with the non-infected control after 15 and 30 days, respectively. Polyphenol oxidase increased by 2 and 1.4 times compared with the non-infected control after 15 and 30 days, respectively. The fungicide also contributed to increasing total phenol content in tomato plants by 25.5 and 72.6% compared with the non-infected control after 30 to 60 days of treatment, respectively. هدف هذ البحث لدراسة تأثير مبيد فوستيل الألمنيوم في نمو المشيجة الفطرية وإنتاش الأبواغ الكونيدية لخمس عزلات من الفطر Fusarium oxysporum f.sp. lycopersici مخبرياً في جامعة تشرين، كلية الزراعة، مخبر المبيدات خلال عامي 2017 و2018م، حيث استخدم المبيد بتراكيز مختلفة تراوحت بين 1 و2000 جزء بالمليون مادة فعالة ضمن المستنبت الغذائي. كما درس تأثير المبيد في الحد من الإصابة بمرض الذبول الوعائي نصف حقلياً في بيت محمي في منطقة جبلة خلال ربيع عام 2018، حيث طبق المبيد بشكل علاجي عن طريق الري، ودرس دوره في تحفيز بعض مؤشرات المقاومة. ظهر تأثير المبيد مخبرياً فقط عند التركيز 2000 جزء بالمليون، حيث ثبط النمو بنسب تراوحت بين 17.9 و42.3% وثبط إنتاش الأبواغ بنسب تراوحت بين 14.5 و20.4%. وبلغت فاعلية المبيد نصف حقلياً 65.34% بعد 60 يوماً من المعاملة. لقد كان للمبيد دوراً مهماً في تحفيز نشاط أنزيمي البيروكسيداز وبولي فينول أوكسيداز خلال 15 و30 يوماً من المعاملة، حيث زاد نشاط أنزيم البيروكسيداز بمعدل 2.54 و2.07 مرة بالمقارنة مع الشاهد السليم على التوالي بعد 15 و30 يوماً، وزاد نشاط أنزيم بولي فينول أوكسيداز بمعدل 2 و1.4 مرة بالمقارنة مع الشاهد السليم على التوالي بعد 15 و30 يوماً. كما ساهم في زيادة محتوى الفينول الكلي في نباتات البندورة بنسبة 25.5 و72.6% بالمقارنة مع الشاهد السليم على التوالي بعد 30 60 يوماُ من المعاملة.